ANALISIS PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, MODAL SOSIAL DAN MODAL FINANSIAL TERHADAP KINERJA UMKM BIDANG GARMEN DI KABUPATEN KLATEN - Rapih, Subroto; Martono, Trisno; Riyanto, Guntur (Jurnal Pendidikan Insan Mandiri, 2015)
The purpose of this study is to analyze and determine (1) The effect on the performance of SMEs HR competence in the field of garment Klaten district. (2) The effect of social capital on the performance of SMEs in the garment district of Klaten. (3) The effect of financial capital on the performance of SMEs in the garment district of Klaten. (4) The effect of human resource competencies to the financial capital of SMEs in the garment district of Klaten. (5) the effect of social capital on financial capital of SMEs in the garment field kbaupaten Klaten. The method used in this research is descriptive quantitative. The population in this study is the garment sector SMEs in Klaten District. Data analysis in this study using Structural Equation Modeling (SEM). The sample in this study of 160 SMEs in the field of garment Klaten that dispersed into 5 clusters. The sampling technique used is the cluster area sampling technique. Techniques of data collection using questionnaire instrument with a Likert scale. The data obtained in this study is primary data obtained directly by distributing questionnaires to the respondents. Prerequisite test SEM analysis used in this research include: sample adequacy test assumptions, normality test and evaluation of outliers. Testing the suitability of the model using a x2 test - Chi-Square statistic, RMSEA (Root Mean Square Error of Approximation), GFI (Goodness of fit index), AGFI (Adjusted Goodness of Fit Index), CMIN / DF (The Minimum Sample Discrepancy Function devided with degrre of Freedom), TLI (Tucker Lewis Indeex), CFI (Comparative Fit Index). Hypothesis test used path analysis suitability. Based on calculations concluded that: (1) the variable Human Resources competencies have significant positive effect on SME performance variable with a value of 4557 and significant at p <0.05, (2) the social capital variables have a significant positive effect on the performance of SMEs variable with a value of 3.599 and was significant at p <0.05, (3) the financial capital variables have a significant positive effect on the performance of SMEs with a value variable sebesarn 4.334 and significant at p <0.05, (4) the HR competency variables have a significant positive effect on the financial capital variables with a value of 3.554 and significant at p <0.05, (5) the social capital variables have a significant positive effect on the financial capital variable with a value of 3.388 and significant at p <0.05.Keywords: Human Resources Competency, Social Capital, Financial Capital, SME Performance